Methodological and Technological Advances in Death Investigations : Application and Case Studies - Ross, Ann H.; Byrd, Jason H. (London: Academic Press, 2023)
Methodological and Technological Advances in Death Investigations: Application and Case Studies focuses on advancements in both methods and technology in death investigations. Specifically, in the areas of latent fingerprints, facial recognition, wildlife forensics, using aerial vehicles and 3D-ID. The combination of national and international authors and a discussion of the state of forensic science over a decade after the National Academies 2009 Report, Strengthening Forensic Science in the United States: A Path Forward, further highlights the boundaries, limitations and context in which these newer technologies and applications act synergistically to enhance forensic science.
Includes index
Keywords: Forensic pathology; Forensic sciences; Death$1 (BInvestigations; Crime scene investigations; Autopsy$1 (BMethodss -- Technology$1 (BForensic applicationss